The complete chloroplast genome of Camellia huulungensis Rosmann et Ninh, a golden Camellia species endemic to Vietnam - Xingwen Zhou; Fangyi Wang; Yiqing Xie; Jing Ning; Yuanfeng Xiao; Changjie Jiang; Guochang Ding; Yunxia Tang (Mitochondrial DNA. Part B. Resources)
Camellia huulungensis Rosmann & Ninh 1997, belonging to the sect. Chrysantha, holds important ornamental value and medicinal value. In this study, the complete chloroplast genome sequence of C. huulungensis was assembled using high-throughput sequencing technology. The entire length of chloroplast genome is 156,546 bp and contains a small single-copy region (18,257 bp), a large single-copy region (86,219 bp), and a pair of inverted repeat regions (26,035 bp). A total of 133 genes were annotated, including 88 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The overall GC content is 37.33%. The phylogenetic analysis showed that C. huulungensis is sister to C. aurea. The results can provide genetic data for further phylogenetic studies of Camellia.